KONTRIBUSI SELF-CONTROL DAN ACADEMIC STRESS TERHADAP CYBERLOAFING PADA MAHASISWA UNIVERSITAS X - Rahmadhani, Amalia; Juwita, Silvi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cyberloafing or the use of the intenet for non-academic purpose during class is becoming increasingly prevalent among college students and has negative impact on academic productivity. This study aims to determine the contribution of self-control and academic stress to cyberloafing among students at X University. The study employed a quantitative approach using multiple linear regression and involved 399 students selected through quota sampling. The results indicate that self-control and academic stress simultaneously contribute significantly to all dimensions of cyberloafing (p = 0,000). Partially, self-control contributes significantly and negatively to the dimensions of sharing (t = 2,692), accessing online content (t = 4,390), and gaming/gambling (t = 2,289), but not significantly to shopping and real-time updating. Academic stress partially contributes significantly and positively to all dimensions of cyberloafing. These findings indicate that self-control and academic stress play a significant role in the emergence of cyberloafing behavior among students during lectures.